Hot Topics in Neural Membrane Lipidology - Farooqui, Akhlaq A. (Springer New York : Imprint: Springer, 2009)
Not only do glycerophospholipid, sphingolipid, and cholesterol-derived lipid mediators facilitate the transfer of messages from one cell to another, they also facilitate communication among subcellular organelles. Hot Topics in Neural Membrane Lipidology provides readers with a cutting-edge, comprehensive review of these lipid mediators, their roles and association with neurological disorders, and the future direction of research on the topic. This monograph provides readers with critical data and is particularly accessible to neuroscience graduate students, teachers, and researchers. It can be used as a supplemental text for a range of neuroscience courses. Clinicians and pharmacologists will find this book useful for understanding molecular aspects of lipid mediators in acute neural trauma like stroke, spinal cord trauma, head injury, and neurodegenerative diseases such as Alzheimer disease, Parkinson disease, and Huntington disease. About the Author: Akhlaq A. Farooqui is a leader in the field of brain phospholipases A2, bioactive ether lipid metabolism, and glutamate-mediated neurotoxicity. He has discovered the stimulation of plasmalogen-selective phospholipase A2 activity in brains from patients with Alzheimer disease, and published cutting edge research on the generation and identification of glycerophospholipid, sphingolipid, and cholesterol-derived lipid mediators in kainic acid neurotoxicity. Dr. Farooqui has authored three monographs: Glycerophospholipids in Brain: Phospholipase A2 in Neurological Disorders (2007); Neurochemical Aspects of Excitotoxicity (2008); and Metabolism and Functions of Bioactive Ether Lipids in Brain (2008). All monographs are published by Springer, New York.